Urinary mutagenicity and genotoxic risk in children with psoriasis after therapeutic exposure to polycyclic aromatic hydrocarbons and ultraviolet radiation - Borska, Lenka; Smejkalova, Jindra; Cerna, Milena; Hamakova, Kvetoslava; Kucera, Ivan; Kremlacek, Jan; Pelikanova, Denisa; Fiala, Zdenek (Mutation research, 2010)
The Goeckerman regimen (GR) for the treatment of psoriasis comprises dermal application of crude coal tar (polycyclic aromatic hydrocarbons, PAHs) and exposure to ultraviolet radiation (UVR). PAHs and UVR are mutagenic and carcinogenic agents. We evaluated dermal absorption of PAHs as well as the mutagenic and genotoxic effects of GR in 16 children with psoriasis, by determining levels of 1-hydroxypyrene (1-OHP), 1-,2-,3-,4-hydroxyphenanthrene, (1-OHPhe, 2-OHPhe, 3-OHPhe, and 4-OHPhe), urinary mutagenicity (Salmonella mutagenicity assay, Ames test) and numbers of chromosomal aberrations in peripheral lymphocytes (CA), in urine and/or blood, before and after GR. The Psoriasis Area and Severity Index (PASI) score was used to evaluate clinical efficacy of GR. Compared with pre-treatment levels, there were significant increases in urinary concentrations of 1-OHP (p<0.001), 1-OHPhe (p<0.001), 2-OHPhe (p<0.001), 3-OHPhe (p<0.001), and 4-OHPhe (p<0.01), indicating a high degree of dermal absorption of PAHs. There were also significantly increased numbers of revertants in the Ames test in two different strains (YG1041-S9, p<0.01; YG1041+S9, p<0.001; TA98+S9, p<0.01), which demonstrates urinary mutagenicity. We also found a significant increase in the number of CA (p<0.001) and significantly decreased number of CA (p<0.01) at 81 days post-treatment, suggesting that GR has a temporary genotoxic effect. The PASI scores were significantly decreased after GR (p<0.001), confirming the clinical benefit of GR. In conclusion, our results demonstrate mutagenic and temporary genotoxic effects of GR in the group of 16 treated child patients.
Keywords: kombinovaná terapie; poškození DNA; Male; Combined Modality Therapy; Child, Preschool; Mutagenicity Tests; DNA Damage; psoriáza; Adolescent; Ultraviolet Therapy; aplikace kožní; Child; dehet uhelný; dítě; Creatinine; mužské pohlaví; Mutagens; polycyklické aromatické uhlovodíky; mladiství; terapie ultrafialovými paprsky; ultrafialové záření; předškolní dítě; mutageny; testy genotoxicity; lidé; Psoriasis; ženské pohlaví; Humans; kreatinin; Ultraviolet Rays; kožní absorpce; Skin Absorption; Female; Polycyclic Aromatic Hydrocarbons; Coal Tar; Administration, Cutaneous